Burnout and risk factors among anesthesia residents and fellows in a conflict-affected context: A national cross-sectional survey - Vanda Yazbeck Karam; Zeina Akiki; Wael Salame; Georges Assaf; Caroline Chahine; Rony Nawwar; Micheline Boukhalil; Hanane Barakat (PLoS ONE, 2025)
Background Burnout is an occupational hazard caused by chronic exposure to excessive work-related stress, negatively impacting both clinicians’ well-being and patient safety. Anesthesiology is particularly demanding, and this stress is further exacerbated in regions affected by conflict, where residents and fellows are confronted with additional stressors beyond the usual challenges of medical training. This study aims to assess the proportion and predictors of burnout among anesthesia residents and fellows in Lebanon, a conflict-affected context, by identifying specific drivers of burnout in this population, while also evaluating their association with sociodemographic characteristics. Methods A cross-sectional study involving electronic, voluntary, and anonymous survey was sent to all Lebanese anesthesiology residents and fellows at all levels of training, between May and October 2024. The survey utilized the Copenhagen Burnout Inventory (CBI) in addition to other questions. Bivariate and multivariable analyses identified predictors of CBI subscales (personal, work-related, and client-related burnout respectively). An alpha of 0.05 was used to determine statistical significance. Results Approximately 71% of participants reported personal burnout, with 32% classified as having a high level. Additionally, 68% reported work-related burnout, with 22% in the high category, and 36% experienced client-related burnout, with 5% classified as high. Moreover, experiencing mental health problems, reporting the need for pharmaceutical or psychological assistance, living with family and covering night shifts were found to be significantly and positively associated with different burnout dimensions. Conclusion Burnout levels among anesthesiology residents in conflict-affected areas appear elevated in reference to international studies, which is concerning given the additional stressors associated with ongoing regional conflict. The continuous escalation of these challenges is likely to exacerbate burnout over time. Targeted interventions to manage burnout are crucial for trainees’ well-being and the effective functioning of medical institutions, particularly in conflict-affected regions where the stressors are compounded.